Description of a new species of Pleseobyrsa (Heteroptera: Tingidae) from Costa Rica - Montemayor Borsinger, Sara Itzel (2011)
A new Pleseobyrsa, P. persea n. sp. is described for Costa Rica. The host plant of this new species is Persea americana P. Mill. This corresponds to the second species of the genus known for the country and the third whose host plant is P. americana (avocado). A description of the adult as well as of instar V are provided, together with a key to species, photographs taken in the field, and illustrations of the fifth nymph stage, adult, and the main characters.